The production of cobalt sulfide/graphene composite for use as a low-cost counter-electrode material in dye-sensitized solar cells - Wang, G.; Zhang, J.; Kuang, S.; Liu, Shaomin; Zhuo, S. (Elsevier SA, 2014)
Cobalt sulfide (CoS)/graphene composites are prepared by a facile one-pot hydrothermal method in the presence of graphene oxide and used as a low-cost substitute for Pt to fabricate the counter electrode in dye-sensitized solar cells. TEM, SEM and AFM characterizations show that CoS nanoparticles are highly dispersed on the surface of graphene nanosheets. This unique nanostructure affords a promising synergistic effect on electrocatalytic performance for the iodide/triiodide redox reaction. Electrochemical impedance spectroscopy and Tafel polarization analyses confirm that the CoS/graphene composite indeed provides simultaneously superior electrocatalytic activity and enhanced electrical conductivity as the counter electrode for dye-sensitized solar cells. Under an illumination of AM 1.5 simulated solar light (100 mW cm−2), the dye-sensitized solar cell based on the CoS/graphene composite counter electrode achieves a conversion efficiency of 7.08%, which is comparable to that of the cell based on Pt electrode and much higher than those of the devices with CoS and graphene electrodes.